ANALISIS NILAI EDUKATIF DALAM NOVEL “GALAU DAN SAJADAH HIJAU” KARYA MUHAMMAD FAISHAL - Wahidah Nasution (Master Bahasa, 2022)
This study aims to explain educational values found in the novel "Galau dan Sajadah Hijau". The method used to analyze educational values in the novel "Galau dan Sajadah Hijau" by Muhammad Faisal, namely descriptive method. The data collection technique used is document analysis. The document was analyzed by reading repeatedly, marking, and classifying educational values. Based on the results of the study show that educational values found in the novel "Galau dan Sajadah Hijau" by Muhammad Faishal include four values, namely religious, moral, social and cultural. Religious values include belief in the provisions of Allah SWT, always subject to him and obey him, and believe and obey his orders. Moral value includes respecting older people, having respect and respect, getting to know women in Taaruf, have an independent attitude, hard worker, devoted to both parents by obeying all parents' advice, diligently learning to achieve their dreams, likes to help parents, generous likes to help weak people, not arrogant, and sincerity in Receive a partner. Cultural value includes expecting the blessing of parents to the actions taken, consider parents as a guiding figure in the search for a mate. Social values include attitudes according to life norms, personality socializing, migrating, and going home for confleasing